2011
DOI: 10.1111/j.1365-2966.2010.18191.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of radio sources in the UKIDSS-DXS-XMM-LSS field

Abstract: The definitive version can be found at: http://onlinelibrary.wiley.com/ Copyright Royal Astronomical SocietyWe investigate the cosmic evolution of low-luminosity (L-1.4 GHz < 1025 W Hz-1 sr-1) radio sources in the XMM Large Scale Structure Survey (XMM-LSS) field. We match low-frequency-selected (610-MHz) radio sources in the XMM-LSS field with near-infrared K-band observations over the same field from the UKIRT Infrared Deep Sky Survey. We use both the mean V/V-max statistic and the radio luminosity function o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Smolčić et al (2009) produced 1.4 GHz luminosity functions using the VLA-COSMOS survey for AGN with 10 21 < L1.4−GHz < 10 26 W Hz −1 to z = 1.3 and found modest evolution, with L ∝ (1 + z) 0.8±0.1 , or Φ ∝ (1 + z) 1.1±0.1 , assuming pure luminosity and density evolution respectively. McAlpine & Jarvis (2011) found that low-luminosity sources evolve differently from their high-luminosity counterparts out to a redshift of z = 0.8 and the measured radio luminosity function was found to be consistent with an increase in the comoving space density of low-luminosity sources by a factor of 1.5. Simpson et al (2012) using deep S1.4 > 100 µJy radio imaging in the Suburu/XMM-Newton Deep Field, produced 1.4 GHz luminosity functions divided into the radio-loud and radio-quiet AGN populations.…”
mentioning
confidence: 70%
“…Smolčić et al (2009) produced 1.4 GHz luminosity functions using the VLA-COSMOS survey for AGN with 10 21 < L1.4−GHz < 10 26 W Hz −1 to z = 1.3 and found modest evolution, with L ∝ (1 + z) 0.8±0.1 , or Φ ∝ (1 + z) 1.1±0.1 , assuming pure luminosity and density evolution respectively. McAlpine & Jarvis (2011) found that low-luminosity sources evolve differently from their high-luminosity counterparts out to a redshift of z = 0.8 and the measured radio luminosity function was found to be consistent with an increase in the comoving space density of low-luminosity sources by a factor of 1.5. Simpson et al (2012) using deep S1.4 > 100 µJy radio imaging in the Suburu/XMM-Newton Deep Field, produced 1.4 GHz luminosity functions divided into the radio-loud and radio-quiet AGN populations.…”
mentioning
confidence: 70%
“…The weaker evolution seen in the FR I population (e.g. Clewley & Jarvis 2004; McAlpine & Jarvis 2011) is therefore a consequence of these objects being exclusively low‐luminosity sources. This view is supported by recent studies which show that FR I and FR II sources of similar luminosities display similar evolution (Rigby, Best & Snellen 2008), and suggests that a complete understanding of radio source evolution can only be obtained with the benefit of significant complementary data to aid in the classification of sources.…”
Section: Introductionmentioning
confidence: 99%
“…Clewley & Jarvis (2004) used the V/V max test to show that low luminosity radio sources evolve differently from their more powerful, predominantly Fanaroff-Riley type II (FRII). McAlpine & Jarvis (2011) used V/V max test to investigate the cosmic evolution of low luminosity (L 1.4 GHz < 10 25 W Hz 1 sr 1 ) radio sources in the XMM Large Scale Structure survey field (XMM-LSS).…”
Section: Introductionmentioning
confidence: 99%